PERKEMBANGAN TEKNOLOGI INFORMASI DAN MANAJEMEN PENGETAHUAN PADA PERPUSTAKAAN DIGITAL DI PERPUSTAKAAN NASIONAL REPUBLIK INDONESIA - Al Qohirie, Mohammad Irfan; Mibari Puspitasari, Ekas; Anggraini Siregar, Fitri (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2024)
This study uses a literature review method, where the data obtained comes from various literatures relevant to the topic discussed. The data is then analyzed and compiled to draw appropriate conclusions. The results of the study indicate that technology and knowledge management have a crucial role in managing digital libraries. With a good management system, librarians can develop skills in managing libraries and create digital library systems that are easier to use and access by users. The design of a digital library information system includes the preparation of a framework and infrastructure that allows for effective and efficient management of information access through digital platforms. One of the main challenges often faced by digital libraries is the difficulty in adapting to developments in information technology and competition with various sources of digital information available in electronic media.